Saving seeds : the gardener's guide to growing and storing vegetable and flower seeds - Rogers, Marc (Storey Communications, 1990)
Saving seeds is a time-honored tradition that many gardeners are rediscovering. Anyone can become a successful seed saver - the only limitations are your time, space, and interest. And the benefits of growing and storing your own seeds are many. Detailed seed information for each vegetable and flower gives you everything you need to know about how to raise, harvest, and store seeds for a lifetime of fruitful home gardening.--COVER.